Exploring The Wellbeing Of Family Caregivers Of Women With Advanced Breast Cancer A Study In The Accra Metropolis - Alomele, B. (University of Ghana, 2017)
Breast Cancer is the leading cause of death and most commonly diagnosed cancer in women. In the advanced stage of the disease, the involvement of the family is required in the care of the patient at home. Advanced Breast Cancer (ABC) does not affect the woman alone but also the wellbeing of the family caregiver. The purpose of this study was to explore the wellbeing of family caregivers of women with advanced breast cancer in the Accra Metropolis. The Quality of Life Model Applied to Family Caregivers by Betty Ferrell (1991) was the organizing framework for this study. A qualitative exploratory descriptive design was employed. A purposive sampling technique was used and data were saturated with the thirteenth participant. Data were collected with a semi-structured interview guide. All interviews were audio taped and transcribed verbatim. Data were analyzed using thematic content analysis. During the study, anonymity and confidentiality were ensured. The four themes stipulated by the model; the physical, social, psychological and spiritual well-being of family caregivers was identified. Emerging themes were beliefs about breast cancer, other sources of treatment and support. Most of the caregivers experienced body pain, sleep disruption, fatigue, and loss of appetite. They assisted their sick relatives with activities of daily living. Their social wellbeing was affected by Isolation, financial burden, secrecy and employment challenges. Psychologically, they expressed fears, were depressed, lost concentration, were empathetic and were anxious. Spiritually, caregivers sought meaning to sick relatives’ illness by questioning God, became more religious and developed positive attitudes. The caregivers had different beliefs about the cause of breast cancer; sought other forms of treatment for their patients and received support from church and family members. It was recommended that caregivers be counseled and educated.
Thesis (MPhil)
Keywords: Wellbeing; Family Caregivers; Women; Advanced Breast Cancer; Accra Metropolis; Ghana